Review: Gablánach in Scélaigecht. Celtic Studies in honour of Ann Dooley, ed. by Sarah Sheehan, Joanne Findon and Westley Follett - Hayden, Deborah (Studia Celtica Posnaniensia, 2016)
Review: Gablánach in Scélaigecht. Celtic Studies in honour of Ann Dooley, ed. by Sarah Sheehan, Joanne Findon and Westley Follett (Dublin: Four Courts Press, 2013), xiv + 282 pp. ISBN 978-1-84682-386-2. Review by DEBORAH HAYDEN, Maynooth University.